Pelatihan Penulisan Dan Submit Artikel Ilmiah melalui Online Journal Sisitem (OJS) Bagi Mahasiswa Akhir Program Studi Teknik Mesin Seluruh Perguruan Tinggi di Aceh - Bachtiar, Dandi; Putra, T. Edisah; Zulfadhli; Akhyar; Arhami; Sari, Ratna; Syuhada, Ahmad; Thaib, Razali (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2023)
The partner in this program is a collaboration with the Mechanical Students Association (HMM) of all universities studying in the Mechanical Engineering study program which is currently completing its final project in Aceh. The partner's problem is the lack of ability to write scientific articles, and, not knowing how to submit scientific articles via OJS (Oper Journal System), and the solution offered is to provide an introduction to strategies for writing scientific articles and the OJS stages in the journal publishing process, provide training in creating author accounts at OJS, providing training on submitting scientific articles through OJS, outreach on how to write scientific articles, as well as training on writing scientific articles. The results of service activities are that partners can recognize OJS and the OJS stages in the journal publishing process, partners have author accounts and can submit scientific articles to OJS, partners can write scientific articles well and correctly. Monitoring and evaluation are also carried out for the sustainability of further activities to resolve partner problems.